2003
DOI: 10.1002/chin.200304228
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Transition Metal Colloids: A Novel Family of Reusable Catalysts?

Abstract: For Abstract see ChemInform Abstract in Full Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 1 publication
0
8
0
1
Order By: Relevance
“…1a) (13). Additionally, nanomaterials have recently been a rapidly growing field involving the use of nanoparticles as catalysts for a variety of organic and inorganic reactions (14,15). Recently, CL studies have been extended to nanoparticles systems, which can participate in CL reactions as a reductant, catalyst and luminophor.…”
Section: Introductionmentioning
confidence: 99%
“…1a) (13). Additionally, nanomaterials have recently been a rapidly growing field involving the use of nanoparticles as catalysts for a variety of organic and inorganic reactions (14,15). Recently, CL studies have been extended to nanoparticles systems, which can participate in CL reactions as a reductant, catalyst and luminophor.…”
Section: Introductionmentioning
confidence: 99%
“…Metal supported nanoparticles are the most common heterogeneous catalysts used in industry. [1][2][3] They are used in a broad range of applications, such as the methane conversion processes, [4 -9] biomass transformation, [10,11] or fine chemical synthesis. [12,13] Numerous parameters influence the performances of these catalysts, such as the type of support, [14,15] the metal nanoparticles size, [16,17] and their interaction with the support.…”
Section: Introductionmentioning
confidence: 99%
“…The reduction of metal ions by an ultrasonic radiation method has been used to a smaller extent to prepare surfactant or polymer‐stabilised metal NPs [14], such as silver [15, 16], gold [17, 18] and platinum [19, 20]. At the same time, ultrasonic wave radiation methods are able to create narrow metal particle sizes [21]. Nagata et al .…”
Section: Introductionmentioning
confidence: 99%
“…[23] reported that fine particles of palladium are readily produced under sonication conditions. Gedanken reported on the preparation of Ni, Cu, Pd or Fe particles by the same procedure, and that a smaller size and greater surface area than those reported can also be obtained [21]. At present, there are few studies that attempt to generate the desired AgNPs by sonochemical radiation; both reducing agents and stabilising agents are needed during ultrasonic radiation and existing research needs to be improved further [24, 25].…”
Section: Introductionmentioning
confidence: 99%